2015
DOI: 10.1111/nep.12489
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell involvement in the progression of peritoneal fibrosis in rats with chronic renal failure

Abstract: This study demonstrated for the first time that the number of mast cells was significantly increased in the fibrotic peritoneum of CRF rats. The proliferation of mast cells and their increased activity in the peritoneum were thought to be responsible for the progression of peritoneal fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 29 publications
3
31
2
Order By: Relevance
“…The mast cell suspension was scattered in a chamber placed on the headstage of an inverted microscope (Nikon, Tokyo, Japan). As we carefully showed in our previous studies [13,14,18], single mast cells were easily distinguishable from other cells by their intracellular inclusion of secretory granules [13,14] or the positive staining for toluidine blue [18]. as described in our previous studies [13,14].…”
Section: Cell Sources and Preparationmentioning
confidence: 91%
See 1 more Smart Citation
“…The mast cell suspension was scattered in a chamber placed on the headstage of an inverted microscope (Nikon, Tokyo, Japan). As we carefully showed in our previous studies [13,14,18], single mast cells were easily distinguishable from other cells by their intracellular inclusion of secretory granules [13,14] or the positive staining for toluidine blue [18]. as described in our previous studies [13,14].…”
Section: Cell Sources and Preparationmentioning
confidence: 91%
“…Therefore, for the treatment or protection against such fibrosis, several pharmacological approaches to inhibit the activation of mast cells have been suggested, including the use of mast cell stabilizers [54,55] or chemokine inhibitors [56,57]. Recently, using rat models of chronic renal failure (CRF), we demonstrated that mast cells proliferated in situ within the fibrotic peritoneum and increased their production of fibroblast-activating factors [18]. Since treatment with tranilast actually ameliorated the progression of peritoneal fibrosis, mast cells were thought to be responsible for the progression of peritoneal fibrosis in CRF.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophils secrete profibrotic cytokines such as IL-13, IL-4, transforming growth factor (TGF)-, and stem cell factor which in turn induce fibroblast and mast cells proliferation and activation (215, 222, 223). Activated mast cells promote tissue remodeling and fibrosis by secreting tryptase, chymase, and histamine, which work closely with fibroblasts (Figure 5) (215, 224226). As seen in the figure, monocytes and macrophages become activated and secrete several inflammatory and toxic mediators including MMPs (200, 227232).…”
Section: The Proposed Mechanisms and Future Perspectives Of Soot- Andmentioning
confidence: 99%
“…Rats with 5/6 nephrectomy and 8‐week recovery periods were used as the model of CRF in the present study. Subtotal nephrectomy was performed in male Sprague–Dawley rats weighing 150–180 g (Japan SLC Inc., Shizuoka, Japan) as described in our previous studies . Briefly, the upper third and lower third of the right kidney were ligated to induce infarction.…”
Section: Methodsmentioning
confidence: 99%
“…CKD is nowadays regarded as a disease of systemic inflammation and several studies recently demonstrated increased activity of peripheral mast cells in addition to T‐lymphocytes or macrophages . In our most recent study, mast cells were actually increased and activated in CRF rat peritoneum, and were thought to be responsible for the progression of peritoneal fibrosis . However, despite accumulating evidence that mast cells may infiltrate into the kidneys with chronic inflammation, we know little about their contribution to the pathogenesis of renal fibrosis associated with CRF.…”
mentioning
confidence: 90%